How do knowledge cycles happen in software development methodologies?. Issue 7 (3rd September 2018) - Balle, Andrea Raymundo; Oliveira, Mírian; Curado, Carla; Nodari, Felipe
Abstract : Purpose: The purpose of this paper is to illustrate how knowledge takes effect in different software development methodologies by relating them to different knowledge cycles. Design/methodology/approach: The results were find by conducing a general review about the topics of knowledge cycles and software development methodologies. Findings: All software development methodologies have knowledge cycles. In Waterfall methodology, the cycle followed is I-Space. For "code and fix, " there is a parallel with March's cycle. Scrum shows a parallel with SECI cycle. Among the methodological options, results show there an increase in hierarchy, documentation, processes and explicit knowledge. Research limitations/implications: Identified parallels of each methodology with knowledge cycles; established which Scrum artifacts are performed at each stage of SECI, which Waterfall steps correspond to I-Space phases and which activities in "code and fix" deal with exploration and exploitation of knowledge; and features shown increase or decrease according to the adoption of each methodology. Practical implications: Results help knowledge sharing implementations and foster inter-team knowledge sharing, with the identification of the correct methodology-cycle match and the personalization of the strategy for each team based on the adopted methodology. Training for knowledge initiatives can be improved by determining how knowledge-sharing activities are incorporated on the determined series of actions established by the methodologies adopted on the firm. Originality/value: The identification of how knowledge is generated and shared among teams in each methodology, the optimum pairing of the methodology and the parallels with the other, and the differences that emerge from the adopted knowledge cycle show that software projects are embedded in a knowledge cycle.